BUDIDAYA DAN PENGOLAHAN PASCA PANEN TANAMAN ROSELLA (HIBISCUS SABDARIFFA) SEBAGAI SIRUP HERBAL - Maulina, Ni Made Intan; Budiyani, Ni Komang (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
Rosella is a shrub or shrub which is a seasonal plant. The rosella plant has many benefits ranging from stems that can be used as gunny sacks, leaves that can be used as cosmetics and flowers that have various properties. The purpose of this research is to increase knowledge and understanding of the processing of post-harvest horticulture products. Increase understanding of the relationship between theory and its direct application. Data collection techniques through observation, the stage of direct observation in the field regarding all activities starting from seeding, harvesting, processing into herbal medicines to packaging. Implementation, carrying out several Rosella plant cultivation activities directly in the field, especially seeding, planting, watering, maintenance and harvesting. Interview, ask directly to the companion or manager. The results showed that rosella cultivation includes seeding, transplanting seedlings, fertilizing, irrigation, pest and disease control. And harvesting. Post-harvest processing of Rosella to become a processed Herbal Syrup Product through several processes including separation of petals from seeds, washing, boiling and packaging.